2021
DOI: 10.1186/s12957-021-02192-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect and limitation of neoadjuvant chemotherapy for pancreatic ductal adenocarcinoma: consideration from a new perspective

Abstract: Background Effect of neoadjuvant chemotherapy (NAC) for pancreatic ductal adenocarcinoma (PDAC) has remained under investigation. We investigated its effect from a unique perspective and discussed its application. Patients and methods We retrospecively analyzed consecutive 131 PDAC patients who underwent pancreatoduodenectomy and distal pancreatectomy. Clinicopathologic data at surgery and postoperative prognosis were compared between patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 27 publications
0
7
0
Order By: Relevance
“…In contrast, significant differences were not observed in other histopathologic features, such as vessel and perineural invasion and differentiation grade, suggesting that NAT only has a limited effect on macroscopically undetectable features, such as control of micrometastases and devitalizing tumor cells in most patients. [27] In other controlled studies, significant differences were observed. Some studies reported a smaller tumor size, better R0 resection rate, and lower lymph node metastasis rate in the NAT group; however, the resection rate was significantly lower.…”
Section: Resection Rate Resection Margin and Lymph Node Metastasismentioning
confidence: 87%
See 1 more Smart Citation
“…In contrast, significant differences were not observed in other histopathologic features, such as vessel and perineural invasion and differentiation grade, suggesting that NAT only has a limited effect on macroscopically undetectable features, such as control of micrometastases and devitalizing tumor cells in most patients. [27] In other controlled studies, significant differences were observed. Some studies reported a smaller tumor size, better R0 resection rate, and lower lymph node metastasis rate in the NAT group; however, the resection rate was significantly lower.…”
Section: Resection Rate Resection Margin and Lymph Node Metastasismentioning
confidence: 87%
“…Although the pathological outcome was better, no survival benefit was seen in NAT patients; in fact, Barbier et al [30] found long-term survival was slightly better in the surgery-first group. [58] Suzuki et al [26] did not recommend GS NAT, and Kurata et al [27] recommended that NAT may be applied to borderline resectable and locally advanced PDAC to enable surgical resection, but upfront surgery was desirable for primary resectable PDAC. No difference in the mOS was observed in the Palmer et al [23] study either.…”
Section: Survivalmentioning
confidence: 99%
“…However, Suker et al [ 35 ] found that FOLFIRINOX could prolong the overall survival of patients with locally advanced PC by comparison of FOLFIRINOX and gemcitabine. Interestingly, two studies of neoadjuvant chemotherapy based on FOLFIRINOX have also been confirmed to benefit patients with locally advanced PC [ 36 , 37 ]. Furthermore, FOLFIRINOX and nab-paclitaxel + gemcitabine had superior benefits to the other group with regards to survival of patients with metastatic PC, consistent with other recent studies that reported similar findings [ 20 , 23 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The proliferation of PC cells was evaluated with a Cell Counting Kit-8 (C0038, Beyotime) following the manufacturer's instruction. Briefly, 5x10 4 Capan-1 and PANC-1 cells transfected with B7H6-siRNA or scramble siRNA were seeded separately into wells of a 96-well plate and cultured in 100 mL of cell culture media. At the indicated time points, the media were replaced with CCK-8 reagent (10 mL CCK-8 and 90 mL Media), and the cells were incubated for an additional hour.…”
Section: Cell Proliferation Analysis By Cck-8 and Rtcamentioning
confidence: 99%
“…There were 496,000 cases and 466,000 deaths globally in 2021, highlighting PC’s high fatality rate ( 2 ). As patients seldom exhibit symptoms at an early stage, 80% have locally advanced disease or distant metastasis at the time of diagnosis ( 3 , 4 ). Although radical resection is a potential cure for PC (and the only cure as yet) ( 5 ), more than 90% of patients who undergo resection experience tumor relapse and die within 5 years ( 6 ).…”
Section: Introductionmentioning
confidence: 99%